ANALISA POLA SPESIMEN PLASTIK UJI PUKUL CHARPY DENGAN MENGGUNAKAN PRINTER 3D - Etik Puspitasari (INFO-TEKNIK, 2019)
Impact testing is needed to measure the toughness of an object that requires a specimen as material to be requested. Where Impact testing specimens from metal that be moulded by casting cannot be made perfect because the angles of the notch are very difficult to make. For this reason, researchers try to make plastic specimens produced from 3D printers where notches or angles in the test specimens can be made precisely using a 3D printer. The design pattern of the plastic test specimen was made according to ASTM standard and tested using the Charpy test having a length of 73.6 mm, a width of 12.7 mm and a thickness of 10 mm, a notch shaped "V" with an angle of 45 ° alongside a notch height of 2, 54 mm . after that it is drawn 3D using 3D software then saved in STL file format then opened, saved and printed in the default software of the 3D printer. The variables researched are layer thickness and temperature. Analysis of the plastic test specimen by using a 3D printer the first is Failed in Impact testing occurred because the placement of the specimen on the charpy compressive test instrument laying would not be straight with the pendulum. The notch angle should be straight with the pendulum by checking the straight position by being photographed from the back and front of the specimen and pendulum. The second obtains if it gets a gap in the slice of the plastic specimen from the type of layer, the energy provided is smaller so that the energy absorbed can be read in the testing process through charpy. The third the plastic specimens code A and code B is getting more layers, the more energy absorbed. The fourth which shows the difference in the nozzle temperature for the plastic test specimens that are set using a nozzle temperature of 200 ° C, the initial energy given is greater and the specimen is stronger receiving the energy load than test plastic specimen using a 180 ° C temperature nozzle.